2021
DOI: 10.9734/sajrm/2021/v9i330209
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characterization of Bacteria Isolated from the Recreational Sites of Two Rivers in Orashi Region, Rivers State, Nigeria

Abstract: Recreational water bodies are water bodies used for recreational activities such as swimming, surfing, water skiing, water diving and sailing. They include rivers, lakes, beaches, spas and swimming pools. This work was therefore aimed at determining the bacteriological profile of recreational water bodies in Orashi region of Rivers State, Nigeria. Surface water samples were collected from two different sites (Orashi River, Mbiama and Sombreiro River, Ahoada) using standard microbiological methods. Upstream, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…The bacterial population seen in this study have been reported in previous studies, to be associated with to water quality [19,20,21] and as potential human pathogens capable of causing different disease in humans, including swimmers ear as well as skin infections and have been linked with some major outbreaks [22].…”
Section: Discussionsupporting
confidence: 67%
“…The bacterial population seen in this study have been reported in previous studies, to be associated with to water quality [19,20,21] and as potential human pathogens capable of causing different disease in humans, including swimmers ear as well as skin infections and have been linked with some major outbreaks [22].…”
Section: Discussionsupporting
confidence: 67%